PERANCANGAN APLIKASI OPTIMALISASI MUATAN PADA KONTAINER DENGAN ALGORITMA METAHEURISTIC - Irawati Djajadi; Lely Hiryanto; Gunadi Gan (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Container Loading Problem (CLP) is a problem that will occur in loading cargo into a container in which the expected result is that goods can be entered into a container with maximum quantity of cargo and empty space on the container to a minimum. An application of container’s cargo optimization is made in the form of cargo arrangement simulation to cope CLP .The method used is metaheuristics which is the development of heuristic algorithms. This method is used to find a better solution to resolve the problem making the charge that the results obtained are expected to be more optimal with some conditions. Based on the tests performed, the results of metaheuristics is sometimes worst than heuristics related to the amount of cargo that successfully stacked but the position of the resulting preparation is better than stage heuristic seen from the resulting fitness value based on stability, type dan cargo load which stacked.